Isolating and diagnosing the Campylobacter Bacteria Types from Raw Milk and its Products and its Relation to Children Diarrhea - Idriss Saleh Jalil (Journal of Global Pharma Technology, 2016)
The study comprised Isolating and diagnosing the Campylobacter Bacteria Types from Raw Milk and its Products and its Relation to Children Diarrhea. The study is conducted in the Graduate Studies Lab. In the College of Pure Sciences. The researcher compiled (164) samples from various sources comprising of (40) raw milk samples, (40) local white cheese samples, (40) local cream samples compiled from local markets in Baqubah city during the period of time from (1/11/2017 to 15/9/2018), and (44) samples of feces from children with diarrhea (watery, mucoid, bloody) of ages between (3 months to 5 years) in Al-Batoul Hospital for Maternity and Children. Results of the study exposed that (44) samples, with a ratio of (37.0%), showed negative growth to the bacterial plantation, and (90) samples, with a rate of (62.19%) mirrored positive growth to the bacterial plantation. Moreover, it is founded that (65) samples with a ratio of (51.829%) were Campylobacter bacteria as the ratio of isolated bacteria from raw milk reached up to (20) samples with a rate of (50%), (9) samples from local white cheese with a rate of (22.5%) and (8) samples from local cream in a ratio of (20%). It is worth noting that bacteria were diagnosed in terms of ability to live on selective media (Skirrow-Preston) and the second method which is planting on non-selective media (Blood agar, Chocolate agar, Macconkey agar). In addition, the ratios of isolated bacteria from feces samples were, (5) samples of bloody sustenance (11.36%), (19) samples of mucoid sustenance (43.18 %) and (20) watery samples (45.45%). The bacteria were also diagnosed by means of micrography which showed its negativity and positivity towards Gram stein; (92.90%) were negative to Gram stein, while (8.09%) were positive to Gram stain. Furthermore, micrography exposed their negativity to Gram stein and showed its different shapes; Bacillus, Spiral, S-shape and Bird-wing shape. Results showed an increase of bacteria in milk and milk products which included many sicknesses and sitotoxism causes which lead to diarrhea among children. Biochemical and physiological examinations were executed and isolates were oxidase-positive, catalase, urease test, Hippurate hydrolysis test, and growth test within (37o C -42o C) temperatures as well as their tolerance of salinity with concentrations between (1.5 %-3.5%).Isolates were sensitive to Nalidixic acid and resistant to Cephalothin. Keywords: Campylobacter (C. jejuni, C. coli, C. hyointestinalis, C. lari), cadF gene, Diarrhea for children.